Correction to: Ni Flower/MXene-Melamine Foam Derived 3D Magnetic/Conductive Networks for Ultra-Efficient Microwave Absorption and Infrared Stealth (Nano-Micro Letters, (2022), 14, 1, (63), 10.1007/s40820-022-00812-w) - Cheng, Haoran; Pan, Yamin; Wang, Xin; Liu, Chuntai; Shen, Changyu; Schubert, Dirk W.; Guo, Zhanhu; Liu, Xianhu (Nano-Micro Letters, 2022)
The original version of this article unfortunately contained some mistakes. The corrections are updated as follows:
CRIS-Team Scopus Importer:2022-06-03

Electrospun Thermoplastic Polyurethane Fibrous Membrane Decorated with MXene/Carbon Black for Dual-Mode Human Movement Monitoring and Energy Harvesting - Gao, Qingsen; Wang, Xin; Schubert, Dirk W.; Liu, Xianhu (Macromolecular Materials and Engineering, 2024)
Conductive fiber membranes have received widespread attention due to their excellent physical and chemical properties. However, developing conductive fiber membranes for both strain sensing and energy harvesting remains a challenge. Herein, a novel thermoplastic polyurethane (TPU)/polydopamine (PDA)/MXene/carbon black (CB) (TPMC) conductive fibrous membrane is developed by combining electrospinning and layer-by-layer dip-coating processes. The TPMC fibrous membrane can be used as a component of strain sensors and triboelectric nanogenerators (TENG) to achieve dual-mode human motion detection and energy harvesting. The strain sensor boasts a wide operating range (0.5%-195%), excellent sensitivity (with a gauge factor (GF) up to 54 at 50% strain and maximum GF of 6.5×104), fast response (80 ms) and excellent cycle durability (over 10 000 cycles), making it possible to detect slight or heavy human activities under various conditions effectively. Additionally, a single-electrode TENG utilizing the TPMC membrane achieves an output voltage of 115 V, a current of 0.8 µA, and a power density of 68 mW m⁻2, also serving as a self-powered sensor for various movements. The excellent dual-mode sensing and energy harvesting properties make it promising for future high-performance wearable devices.
CRIS-Team Scopus Importer:2025-02-04
Keywords: electrospun fibrous membranes; MXene; strain sensor; triboelectric nanogenerators

Flexible and thin multifunctional waterborne polyurethane/Ag film for high-efficiency electromagnetic interference shielding, electro-thermal and strain sensing performances - Jia, Yunpeng; Sun, Ruizhou; Pan, Yamin; Wang, Xin; Zhai, Zhanyu; Min, Zhiyu; Zheng, Guoqiang; Liu, Chuntai; Shen, Changyu; Liu, Xianhu (Composites Part B-Engineering, 2021)
With the rapid development of the flexible electronics industry, the range of multifunctional applications of materials has become extensive. But it is still a challenge to apply flexible materials to different fields while ensuring corresponding performance. Herein, a simple and available approach is addressed to fabricate conductive polymer composite films supported on Ag flakes and waterborne polyurethane (WPU) by spraying. The WPU/Ag films with uniform structure show outstanding flexibility and electromagnetic interference shielding effectiveness of 68.9 dB with thickness of only 50 μm, and could sustain a high standard even undergoing excessive mechanical deformations. Besides, the resulted films possess prominent electro-thermal effect, which can achieve a temperature of over 120 °C by applying a low voltage of 2 V, and the heat can be dissipated rapidly along with the connecting Ag network. Moreover, it shows a high gauge factor (229.2), good durability and reproductivity (over 1000 cycles), and rapid response time to strain (50 ms), which can be potentially used in the field of human movement monitoring and wearable electronic devices. These results indicate the multifunction of the WPU/Ag film, which could widen its practical applications after the corresponding treatment.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Conductivity; Electromagnetic interference shielding; Joule heating; Polymer composites; Strain sensor

Highly Sensitive Ultrathin Flexible Thermoplastic Polyurethane/Carbon Black Fibrous Film Strain Sensor with Adjustable Scaffold Networks - Wang, Xin; Liu, Xian Hu; Schubert, Dirk W. (Nano-Micro Letters, 2021)
In recently years, high-performance wearable strain sensors have attracted great attention in academic and industrial. Herein, a conductive polymer composite of electrospun thermoplastic polyurethane (TPU) fibrous film matrix-embedded carbon black (CB) particles with adjustable scaffold network was fabricated for high-sensitive strain sensor. This work indicated the influence of stereoscopic scaffold network structure built under various rotating speeds of collection device in electrospinning process on the electrical response of TPU/CB strain sensor. This structure makes the sensor exhibit combined characters of high sensitivity under stretching strain (gauge factor of 8962.7 at 155% strain), fast response time (60 ms), outstanding stability and durability (> 10,000 cycles) and a widely workable stretching range (0–160%). This high-performance, wearable, flexible strain sensor has a broad vision of application such as intelligent terminals, electrical skins, voice measurement and human motion monitoring. Moreover, a theoretical approach was used to analyze mechanical property and a model based on tunneling theory was modified to describe the relative change of resistance upon the applied strain. Meanwhile, two equations based from this model were first proposed and offered an effective but simple approach to analyze the change of number of conductive paths and distance of adjacent conductive particles.[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2021-02-05
Keywords: Electronic skin; Electrospinning; Fitting model; Strain sensor

High sensitive electrospun thermoplastic polyurethane/carbon nanotubes strain sensor fitting by a novel optimization empirical model - Wang, Xin; Qu, Muchao; Wu, Kuangqi; Schubert, Dirk W.; Liu, Xian Hu (Advanced Composites and Hybrid Materials, 2023)
A variety of high-performance strain sensors for monitoring changes in physical quantities have attracted considerable interest from academia and industry. In this work, a high sensitive flexible strain sensor is fabricated through electrospun thermoplastic polyurethane (TPU) fibrous film with dip-coating ultrasonication treated carbon nanotubes (CNTs). TPU/CNTs strain sensor exhibits an excellent comprehensive performance of high sensitivity (maximum gauge factor of 1571), outstanding tensile strength and toughness (stress > 24 MPa, strain > 400%), brilliant durability (10,000 cycles at 10% strain) and a widely workable stretching range (0–400%). Based on the properties of high sensitivity, wearable and wide workable, TPU/CNTs strain sensor has been prepared as a simple application for intelligent terminals, e-skins and body activity monitoring. More importantly, this work introduces a novel optimization empirical equation to describe and predict the conductive response on the stretching of the sensor. Compared with the general optimization model, the novel optimization empirical model presents a better fitting degree and more similar to the benchmark mathematic model from tunnelling theory. Furthermore, this model provides a good description of the changes in the conductive pathways during the operation of different sensors as well. Graphical Abstract: Fabrication of high-performance electrospun TPU/CNTs strain sensor and fitting by a novel optimization empirical equation to predict the conductive response. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2023-04-07
Keywords: Electronic skin; Electrospinning technology; High sensitive strain sensor; Novel optimization empirical model

Ni Flower/MXene-Melamine Foam Derived 3D Magnetic/Conductive Networks for Ultra-Efficient Microwave Absorption and Infrared Stealth - Cheng, Haoran; Pan, Yamin; Wang, Xin; Liu, Chuntai; Shen, Changyu; Schubert, Dirk W.; Guo, Zhanhu; Liu, Xianhu (Nano-Micro Letters, 2022)
The development of multifunctional and efficient electromagnetic wave absorbing materials is a challenging research hotspot. Here, the magnetized Ni flower/MXene hybrids are successfully assembled on the surface of melamine foam (MF) through electrostatic self-assembly and dip-coating adsorption process, realizing the integration of microwave absorption, infrared stealth, and flame retardant. Remarkably, the Ni/MXene-MF achieves a minimum reflection loss (RLmin) of − 62.7 dB with a corresponding effective absorption bandwidth (EAB) of 6.24 GHz at 2 mm and an EAB of 6.88 GHz at 1.8 mm. Strong electromagnetic wave absorption is attributed to the three-dimensional magnetic/conductive networks, which provided excellent impedance matching, dielectric loss, magnetic loss, interface polarization, and multiple attenuations. In addition, the Ni/MXene-MF endows low density, excellent heat insulation, infrared stealth, and flame-retardant functions. This work provided a new development strategy for the design of multifunctional and efficient electromagnetic wave absorbing materials.[Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2022-03-11
Keywords: Flame-retardant; Heat insulation; Infrared stealth; Microwave absorption; Ni-MXene/Melamine foam

Polypyrrole Functionalized Graphene Oxide Accelerated Zinc Phosphate Coating under Low-Temperature - Zhu, Qingsong; Liu, Jingguang; Wang, Xin; Huang, Yuxiang; Ren, Ying; Song, Weiqiang; Mu, Chenzhong; Liu, Xianhu; Wei, Fengchun; Liu, Chuntai (ES Materials & Manufacturing, 2020)
Zinc phosphate coating, as an effective and fast anticorrosion technique for the metals, have been developed rapidly in recent years. However, it is still a challenge to synthesize a low energy, environmentally friendly and efficient accelerator through a facile method. Herein, as a new accelerator, polypyrrole (PPy) functionalized graphene oxide (GO-PPy) nanocomposites were prepared by in-situ process to grow PPy film on GO surface, Incorporation of GO-PPy into phosphate baths accelerated the phosphating process of phosphate coating and promoted the nucleation and growth of phosphate crystals, achieving stronger corrosion resistance, which were confirmed by electrochemical measures and morphologies characteristic of the phosphate coating. Additionally, when the concentration of GO-PPy in the phosphate baths reached up 1.2 g/L, the phosphate coating possessed the most compact and uniform phosphate crystals and the best corrosion protection performance. Finally, the special mechanism of the phosphate process was discussed. This work introduces a new, low-energy, facile, environmentally friendly and alternative accelerator for the preparation of phosphate coatings.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Accelerate; Corrosion protection; Phosphate coating; Phosphate crystals

Self-adhesive, stretchable waterborne polyurethane-based flexible film as wearable conformal strain sensor for motion and health monitoring - Xing, Linlong; Wang, Xin; Li, Mingzhan; Jia, Yunpeng; Yang, Guanda; Liu, Chuntai; Shen, Changyu; Liu, Xianhu (Advanced Nanocomposites, 2024)
Wearable tensile strain sensors are of great importance in both motion monitoring and next-generation, personalized health diagnostics. The accuracy, reliability and stability of the signals obtained from these sensors are significantly dependent on the conformal contact between the flexible sensor and the skin surface. In this study, we have developed a flexible double-layer film as a wearable tensile strain sensor by a simple solution-blending method and a layer-by-layer spraying method. D-sorbitol was incorporated into a waterborne polyurethane (WPU) emulsion to enhance film adhesion, achieving a strength of 7.91 N/m, and to disrupt hydrogen bonds between the WPU chains. This disruption facilitates more straightforward conformational changes of the chains under stress, thereby substantially enhancing the mechanical flexibility of the film. The sensing layer was subsequently constructed by spraying silver microparticles, exhibiting extremely high sensitivity (gauge factor = 103.01) over a 19.3% strain range. This sensor can effectively monitor joint motions and subtle muscle movements as tensile strain sensors.<br
Keywords: D-sorbitol; Waterborne polyurethane; Self-adhesive; Strain sensors; Motion and health monitoring

Superior sensitive, high-tensile flexible fabric film strain sensor - Wang, Xin; Liu, Xian Hu; Ge, Xiao; Schubert, Dirk W. (Composites Part A-Applied Science and Manufacturing, 2023)
Developing strain sensor with higher sensitivity and larger monitoring range is urgently needed for meeting the increasing potential applications of high-performance sensors in intelligent electronics, motion signal analysis and human monitoring. Herein, via an advanced and efficient method about embedding silver nanowires on electrospun thermoplastic polyurethane fabric film modified with carbon black, a high-performance flexible strain sensor is fabricated. The strain sensor exhibits excellent electrical response abilities of the superior sensitivity (gauge factor >16,000) with strain of 360%, an ultra-wide strain range (0.1% to 200%) and outstanding durability and reliability (>10,000 cycles) under cyclic stretching-recovering operating. Furthermore, mathematical fitting models about variation of resistance (ΔR/R0) and gauge factor upon the applied strains during the stretching process are proposed, which can quantitatively describe and analysis the variation of conductive pathways and inter-particles distance under the external stimuli. It is expected that such fitting models can be used to predict conductive sensing behaviors of flexible strain sensors for actual manufacturing and improvement of products.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Electrospinning; Fitting models; Silver nanowires; Strain sensor